Prenatal care in urban China: Qualitative study on challenges and coping mechanisms - Haruka Nagao (Elsevier, 2024)
This study aims to identify challenges that women face in accessing prenatal care services in urban China and their coping mechanisms to deal with the challenges. We conducted semi-structured interviews in June and July in 2019 with 38 women who had experience of childbirth within the last five years. Through interviews, this study pays particular attention to a quality of prenatal care services by focusing on women's experiences in seeking for such services. The findings suggest that most participants had access to standardized prenatal care services but faced two challenges: long wait time and short doctor-patient interaction time. These challenges stem from overcrowded hospitals. The findings also illuminate power and information asymmetry between doctors and patients. Women leverage social networks with friends, colleagues, and former classmates to fill in the gap of short doctor-patient interaction by obtaining relevant information about pregnancy and prenatal care services. The analyses of interviews and a social networking site also suggest that online social networks play a similar role to fill in the informational gap. Still, social networks remain a coping mechanism rather than a fundamental solution to the systemic issues within the public health system.